Cost-effectiveness analysis of two inhaled antibiotics for stable Bronchiectasis with Pseudomonas aeruginosa infections in China - Wanxin Chen; Xuerong Chen; Liting Lai; Bin Hong; Canghong Zhi; Honglin Li; Sha Li; Jie Jiang (PLoS ONE, 2025)
Objective To evaluate the cost-effectiveness of two available options for inhaled antibiotic treatment for patients with Bronchiectasis (BE) with Pseudomonas aeruginosa (PA) infections from the perspective of China’s healthcare system. Methods A four-state Markov model was developed over a one-year horizon to simulate the cost-effectiveness of two inhaled antibiotic strategies: Tobramycin inhalation solution (TIS) versus nebulized colistimethate sodium (CMS). The inputs for the model were derived from phase III clinical trials and published literature, with cost data were sourced from public and real-world databases, etc. The incremental cost-effectiveness ratio (ICER) was assessed, setting the willingness-to-pay threshold at one times the per capita GDP of China. Scenario and sensitivity analyses were performed to explore the impact of uncertainties in input parameters. Results Over a one-year period, TIS was found to dominate CMS, resulting in a cost saving of CNY 41,109.53 (USD 5,689.27) and an increase of 0.0048 quality-adjusted life years (QALYs) per patient. Sensitivity analyses confirmed the robustness of these findings, which remained consistent under various scenarios. Conclusions TIS reduces healthcare costs and improves clinical outcomes compared to CMS in managing BE with PA infections in China. This study supports the inclusion of TIS in clinical guidelines for managing BE with PA infections, considering both economic benefits and health outcomes.